Identifying critical weak points of power-gas integrated energy system based on complex network theory - Zhang, Chenwei; Wang, Ying; Zheng, Tao; Wang, Chen; Zhang, Kaifeng (Reliability engineering & system safety, 2024)
•Weighted coupling betweenness is proposed to identify critical weak points in PGIS.•An approximate algorithm of shortest-paths calculations (AA-SPC) is proposed.•Six attack strategies and two vulnerability assessment indicators are developed.•A virtual European PGIS is constructed by combining three types of energy hubs. Prompt and precise identification of critical weak points is essential in integrated energy systems (IES) to mitigate system reliability issues and effectively prevent cascading failures. This study proposes methods to identify critical weak points in the power-gas integrated system (PGIS) based on complex network theory for this task. Firstly, we improve the traditional betweenness indices in complex network theory by integrating power output of energy supply equipment as weighted factors to capture diverse types of energy flows, and incorporating the efficiency coefficient to account for energy losses via the PGIS coupling equipment. By integrating these refinements, our approach could further identify some points that are not weak from the viewpoint of topology but are crucial for energy transmission. Secondly, we propose an approximate algorithm for shortest-paths calculations (AA-SPC), which preserves information of total node and some specific topological, and simplifies the calculation of target shortest path, aiming at increasing the efficiency of obtaining path information. Additionally, vulnerability assessment indicators, including system fragmentation and network betweenness loss, measure PGIS vulnerability under different attack strategies. The aforementioned methods are applied to a self-built virtual European PGIS based on the open-source database SciGRID, successfully identifying critical weak points overlooked by traditional betweenness indices.